CONNECTING THE EDUCATION SYSTEM TO THE LABOR MARKET – PREMISE OF RESPECTING THE RIGHT TO EDUCATION AND THE RIGHT TO WORK (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
This article is based on the link between the right to education, the right to work and the right to an adequate standard of living, all three included in the Universal Declaration of Human Rights. The paper explores the link between education and the labour market, considering that every human being has the right to an education that provide the necessary competencies for a proper integration on the labour market. During the last decades the education became more connected with the economic activity and the economic theories and concepts are widely used in designing and evaluating the educational policy. Concepts such as costs, results, investments, efficiency, competitiveness etc., taken from the economic sphere have been increasingly present with reference to the education institutions or to the education system as a whole. The education is no longer reserved to the elites and because it became a mass process, it is obvious that its main objective should be preparing the futures employees for their potential jobs. Many international organizations (mainly concerned with economic issues) are involved in analyzing and evaluating the national educational systems as well as in providing directions for the educational policy. The economic globalization made most countries interested in their international competitivity and in their position in the global competition and these aspects are related to the efficacity of their educational systems.The statistical data available at the international level proves that the quality of the educational systems is linked with the standard of living of the population. That means that investing in education and properly designing the educational policy might be the most efficient active social protection measures that use efficiently the public resources and offer to each individual the chance for a dignified life.